MEMBANGUN WEBSITE PROGRAM STUDI PSIKOLOGI UNIVERSITAS SAHID SURAKARTA - Sutopo, Agus; Retnoningsih, dwi; Charolina, Astri (Gaung Informatika, 2015)
PsychologyÂ  MajorÂ  ofÂ  SahidÂ  UniversityÂ  SurakartaÂ  isÂ  underÂ  theÂ  FacultyÂ  ofÂ  HealthÂ  Sciences.Â Â  The information about the major is still manual and not effective. According to the improvement of information technology based on internet, website is the right solution to convey information fast and eficiently. The purpose of this researchÂ  is to developÂ  Psychology majorÂ  of Sahid University Surakartaâs website in order to simplify the information management and delivery to the students and the society. The methodsÂ Â  which areÂ  usedÂ  toÂ  collectÂ  theÂ  dataÂ  areÂ  observation,Â  interview,Â  literature,Â  andÂ  questionnaireÂ  methodÂ  toÂ  webQual test. The data analysis used is structured based onÂ  (DFD) Data Flow Diagram, Flowchart. The making of thisÂ  websiteÂ  usesÂ  HTML,Â  PHPÂ  andÂ  MySQLÂ  databaseÂ  programming.Â  ToÂ  measureÂ  theÂ  qualityÂ  ofÂ  the PsychologyÂ  majorÂ  ofÂ  SahidÂ  UniversityÂ  SurakartaâsÂ  website,Â  adjustedÂ  toÂ  theÂ  visitorsâÂ  orÂ  theÂ  lastÂ  userâsperception, so the website test method used is webQual testing and Likert scale. From 30 questions which wereÂ  askedÂ  toÂ  30Â  respondentsÂ  andÂ  theÂ  dataÂ  areÂ  processedÂ  usingÂ  SPSSÂ  20,Â  theÂ  testingÂ  resultÂ  ofÂ  the Psychology Major of Sahid UniversityÂ  Surakartaâs website is 7.14%. ItÂ  means that the Psychology Majorof Sahid University Surakartaâs website is good.